2017
DOI: 10.1515/zna-2016-0377
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Electronic, and Mechanical Properties of CoN and NiN: An Ab Initio Study

Abstract: The structural stabilities of cobalt mononitride (CoN) and nickel mono-nitride (NiN) were investigated among the crystal structures, namely, NaCl (B1), CsCl (B2), and zinc blende (B3). It was found that the zinc blende (B3) phase was the most stable phase for both nitrides. A pressure-induced structural phase transition from B3 to B1 phase was predicted in these nitrides. The computed lattice parameter values were in agreement with the experimental values and other theoretical values. The electronic structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…Though theoretical works predict both ZBand RS-type structures for FeN and CoN, but under ambient temperature and pressure, the ZB-type structure is preferred [21]. The energy minima in the total energy-volume plots is lower in ZB, as compared to that in RS CoN [21,22,[37][38][39][40]. Under high pressure, a phase transition from ZB-to RS-type phase is expected at about 50 GPa in FeN [33] and about 40 GPa in CoN [22].…”
Section: Introductionmentioning
confidence: 93%
“…Though theoretical works predict both ZBand RS-type structures for FeN and CoN, but under ambient temperature and pressure, the ZB-type structure is preferred [21]. The energy minima in the total energy-volume plots is lower in ZB, as compared to that in RS CoN [21,22,[37][38][39][40]. Under high pressure, a phase transition from ZB-to RS-type phase is expected at about 50 GPa in FeN [33] and about 40 GPa in CoN [22].…”
Section: Introductionmentioning
confidence: 93%
“…On the other hand, CoN and NiN have received a little attention from scientific researchers. Structural, electronic, and mechanical properties of CoN and NiN have been investigated in three cubic crystal structure, NaCl, CsCl, and zinc blende (ZB) by Amudhavalli et al [8], and CoN and FeN in ZB and RS structures by Lukashev et al [9] based on the first principle calculation and found stable in ZB structure. Earlier theoretical work, base on the first principle calculation, Liu et al [10] have investigated the structural, mechanical and electronic properties of 3d transition metal nitrides in cubic zincblende, rocksalt and cesium chloride structures and found that these materials are almost stable and hard.…”
Section: Introductionmentioning
confidence: 99%
“…Though theoretical works predict both ZB and RS-type structures for FeN and CoN but under ambient temperature and pressure, the ZB-type structure is preferred [21]. The energy minima in the total energy-volume plots is lower in ZB, as compared to that in RS CoN [21,22,[30][31][32][33]. Under high pressure, a phase transition from ZB to RS-type phase is expected at about 50 GPa in FeN [26] and about 40 GPa in CoN [22].…”
Section: Introductionmentioning
confidence: 99%
“…The energy minima in the total energy-volume plots is lower in ZB, as compared to that in RS CoN [21,22,[30][31][32][33]. Under high pressure, a phase transition from ZB to RS-type phase is expected at about 50 GPa in FeN [26] and about 40 GPa in CoN [22].…”
Section: Introductionmentioning
confidence: 99%